Burnout and Psychological Safety: A Questionnaire Study of Medical Students - Aziz Bitar; Jens Boman; Emelie Kristoffersson (Journal of Medical Education and Curricular Development)
Background Psychological safety—defined as the perception that a group environment is safe for interpersonal risk-taking—could influence the development of burnout among medical students. This study, therefore, sought to investigate the prevalence of burnout, the level of psychological safety, and their association in this population. Methods We surveyed undergraduate medical students ( n  = 944) enrolled in semesters 2 to 10 at a Swedish medical school using a questionnaire containing the Burnout Assessment Tool (BAT-12), Amy Edmondson's Team Psychological Safety Survey, and socio-demographic questions. Data were analyzed using descriptive statistics, t -tests, one-way ANOVA, Pearson's correlation, and hierarchical regression analysis. Results A total of 457 medical students (62.6% women) completed the questionnaire (response rate: 48%). Of the participants, 51.4% scored above the cut-off for burnout risk, and among these, 25.6% were at very high risk. Women scored significantly higher on burnout and lower on psychological safety than men. A significant negative association was found between psychological safety and burnout, with psychological safety accounting for an additional 14.3% of the variance in burnout scores. Conclusions Our findings suggest that more than half of the surveyed medical students are at risk for burnout and that lower levels of psychological safety are associated with higher levels of burnout. Furthermore, women appear to be at higher risk for burnout and perceive medical school as less psychologically safe than male students. While longitudinal studies are needed to assess the causality between low psychological safety and burnout, our results provide impetus for developing interventions to prevent burnout and addressing an eventual lack of psychological safety in medical school.